Head and Neck Warming Applied in Thermoneutral Conditions Improves Thermal Sensation but does Not Alter Cognitive Function - Henrikas Paulauskas; Dalia Mickevičienė; Vaida Berneckė; Kazimieras Pukėnas; Marius Brazaitis (Lithuanian Sports University, 2018)
Background. Heat therapy is widely used for therapeutic purposes in health SPA resorts or hospitals. However, its  benefits  and  consequences  are  not  strongly  evidenced  and  it  is  partially-related  with  a  lack  of  experimental information. No one has explored how continuous head and neck warming applied in thermoneutral environment can affect body temperatures, subjective sensations and cognition and the purpose of this study was to investigate it. Methods.  Seven  subjects  (21  ±  1  years)  participated  in  two  experimental  trials:  CON  -  control  trial;  and CONW - head and neck warming trial. These trials were designed to introduce the effects of continuous head and neck warming (surface warming by 44 ± 1°C) on thermal sensations, body temperatures and cognitive function in thermoneutral environment (24°C and 60% relative humidity). In each trial body temperatures (rectal, Tre; mean skin, Tsk), heart rate (HR) response, ratios of subjective sensations (SS) and cognitive function were assessed. Results. Head and neck warming (CONW trial) maintained significantly higher Tre and Tsk values (by 0.2 ± 0.1°C and 1 ± 0.3 °C, respectively), compared to the control (CON) trial. Head and neck warming caused significant increment in heart rate (8 ± 2 b/min) and improved thermal sensation (p < .05), but had no effect on shivering/ sweating sensation and thermal comfort. Moreover, head and neck warming (CONW trial) does not induce any significant impact on accuracy (p > .05) and response times (p >.05) in mathematical and spatial processing tasks. Conclusions. Continuous head and neck warming applied in thermoneutral conditions maintains higher internal (Tre) and peripheral (Tsk) body temperatures and improves thermal sensation, but does not alter cognitive function. Keywords: head and neck warming, subjective sensations, body temperature, cognitive function.